Vitamin D Status and Its Association with Parathyroid Hormone Concentration in Brazilians - Juliana Sálvio Martins; Magda de Oliveira Palhares; Octávio Cury Mayrink Teixeira; Mariana Gontijo Ramos (Journal of Nutrition and Metabolism)
Vitamins are organic compounds that play a vital role in the control of metabolic processes. The D complex is considered a nutrient with a hormonal action and has an important participation in the constant maintenance of serum and extracellular calcium levels. The present study aims to analyze the results of 105.588 vitamin D (25(OH)D) measurements obtained from a database from a clinical analysis laboratory in Brazil, between the years of 2011 and 2013. The values of 25(OH)D were correlated with age, gender, and values of PTH. The results show a high prevalence of values of 25(OH)D considered inadequate, characterizing 76% of the studied population. It was observed that 26,5% of the individuals had deficiency and 49,5% had insufficiency of vitamin D. It was also shown that there was a negative correlation between 25(OH)D and PTH levels. In conclusion, this study is in accordance with others that show a high prevalence of vitamin D deficiency in different populations and alerts us for the importance of these measurements and analysis in clinical practice and as a base for diagnosis and treatment of hypovitaminosis.